2015
DOI: 10.7314/apjcp.2015.16.4.1571
|View full text |Cite
|
Sign up to set email alerts
|

Does treatment of Helicobacter Pylori Infection Reduce Gastric Precancerous Lesions?

Abstract: Background: Treatment of Helicobacter pylori (H. pylori) decreases the prevalence of gastric cancer, and may inhibit gastric precancerous lesions progression into gastric cancer. The aim of this study was to determine the effect of treatment on subsequent gastric precancerous lesion development. Materials and Methods: We prospectively studied 27 patients who had low grade dysplasia at the time of enrollment, in addition to dysplasia atrophic gastritis and intestinal metaplasia observed in all patients. All wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Antrum and corpus may be different in mRNA expression, change patterns of morphometric features and function of acid secretion during the precancerous lesions, 78–80 which may lead to significant difference in improvement of AG or IM in the antrum versus corpus, but could not explain the nonsignificant difference in the improvement of AG or IM in the antrum versus corpus after H. pylori eradication. In addition, four studies included in this meta‐analysis showed that the improvement of AG and IM discriminated in the greater curvature and the lesser curvature, 36,39,43,81 and all the studies included in this meta‐analysis supported that improvement of AG and IM after H. pylori eradication in greater curvature was more significant than in lesser curvature. Two studies 35,66 focused on fundus and one study 67 focused on angle demonstrated that H. pylori eradication could significantly improve AG but not IM in fundus and angle.…”
Section: Discussionsupporting
confidence: 55%
“…Antrum and corpus may be different in mRNA expression, change patterns of morphometric features and function of acid secretion during the precancerous lesions, 78–80 which may lead to significant difference in improvement of AG or IM in the antrum versus corpus, but could not explain the nonsignificant difference in the improvement of AG or IM in the antrum versus corpus after H. pylori eradication. In addition, four studies included in this meta‐analysis showed that the improvement of AG and IM discriminated in the greater curvature and the lesser curvature, 36,39,43,81 and all the studies included in this meta‐analysis supported that improvement of AG and IM after H. pylori eradication in greater curvature was more significant than in lesser curvature. Two studies 35,66 focused on fundus and one study 67 focused on angle demonstrated that H. pylori eradication could significantly improve AG but not IM in fundus and angle.…”
Section: Discussionsupporting
confidence: 55%
“…Worldwide, it seems that the incidence of Hp infection has an influence upon the types of polyps found in different populations in the west; as Hp infection decreases, fundic gland polyps increase, while in areas such as East Asia, where Hp infection remains common, hyperplastic or neoplastic polyps related to the underlying inflammatory process are more common (18). The level of Hp infection is important because it is an established risk factor for gastric cancer (19), and Hp eradication therapy can effectively reduce the development of precancerous lesions and gastric cancer (20).…”
Section: Discussionmentioning
confidence: 99%
“…En relación a si el tratamiento de erradicación H. pylori pudiera mejorar las lesiones precancerosas, Mansour-Gha- naei F no halló diferencias entre las lesiones metaplásicas previas y dos años después de erradicar H. pylori, aunque otros autores han descrito mejorías, se cree que las diferencias se presentan por el tiempo de seguimiento, el tamaño de las muestras, cantidad y localización de las biopsias y los patrones histológicos de lectura (39).…”
Section: Helicobacter Pylori (+) N=127unclassified